Clinicopathological Characteristics of Cervical Carcinoma with Pelvic Lymph Node Metastases in Dr. Hasan Sadikin General Hospital, Bandung 2013-2021 - Sri Rejeki, Henny; Suryanti, Sri; Yantisetiasti, Anglita; Mantilidewi, Kemala I.; Winarno, Gatot Nyarumenteng Adhipurnawan (Althea Medical Journal, 2023)
Background: Carcinoma of the cervix is the most common gynecological malignancy, which ranks first among carcinomas in Indonesia. Lymph node metastasis is a risk of recurrence, affecting survival and therapy. The purpose of this study was to determine the clinicopathological characteristics of cervical carcinoma with pelvic lymph node metastasis that had undergone radical hysterectomy and lymphadenectomy at Dr. Hasan Sadikin General Hospital, Bandung.Methods: This study used a cross-sectional retrospective descriptive study. Data on the clinical stage I-II cervical cancer patients with pelvic lymph node metastasis were collected  from the archives of the pathological anatomy  laboratory during period from 2013 to 2021. Data were presented in percentage.Results: There were 64 data patients, and the most common age of cervical carcinoma ranged from 40 to 50 years old (52%), the most common stage was stage II (66%), and the most frequent histopathological type was squamous cell carcinoma (70%). The highest degree of differentiation was moderate differentiation (50%). There was no difference in tumor size between sizes <4 cm and ≥4 cm.Conclusion: The cases of cervical carcinoma at Dr. Hasan Sadikin General Hospital Bandung are treated with radical hysterectomy and lymphadenectomy. The patients generally aged between 41–50 years old, stage II, and squamous cell carcinoma with a moderate degree of differentiation.